Implementasi Pengawasan Partisipatif Pemilu oleh Guru Ngaji di Kabupaten Brebes - Lukmanul Hakim; Izzatusholekha Izzatusholekha (Institut Nalanda, 2023)
Election supervision is not only the task of the Election Supervisory Agency (Bawaslu), but the community is expected to play a role in supervising each stage. The role of the community is not only to give their voting rights during the implementation of elections, but also to oversee the process of the election stages. One of them is the role of the recitation teacher of the Diniyah Madrasah (Madin) in Brebes Regency, participating in the socialization of participatory supervision to the community regarding Election Supervision. The Communication Forum of Diniyah Takmiliyah (FKDT) of Brebes Regency participated in the training stage to become an election facilitator held by the Media Nusantara Development Association (PPMN) in collaboration with the Association for Elections and Democracy (Perludem). Furthermore, Bawaslu of Brebes Regency conducted an MoU with FKDT of Brebes Regency regarding the socialization of participatory supervision. FKDT is trained to have the ability to socialize through various means including election graphic design training, election journalists and election facilitators. The follow-up of the socialization is of course so that the community plays a role as a pioneer and reporter of election supervision.